2005
DOI: 10.1128/cdli.12.12.1455-1457.2005
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Severe Acute Respiratory Syndrome (SARS) Coronavirus-Specific Antibody in SARS Patients

Abstract: The serum antibodies to severe acute respiratory syndrome (SARS) coronavirus of 18 SARS patients were checked at 1 month and every 3 months after disease onset. All of them except one, who missed blood sampling at 1 month, tested positive for the immunoglobulin G (IgG) antibody at 1 month. Fifteen out of 17 tested positive for the IgM antibody at 1 month. The serum IgM antibody of most patients became undetectable within 6 months after the onset of SARS. The IgG antibody of all 17 patients, whose serum was che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 14 publications
3
41
0
Order By: Relevance
“…With a large number of patients who had confi rmed transmission history (176) and a complete dataset for 18, the level of confi dence is high that the results obtained in this study are representative for convalescent SARS patients. Similar results have been reported from longitudinal stud-ies of SARS patients with smaller cohort size (18-98 patients) and shorter follow-up period (240 days to 2 years) (9)(10)(11)(12)(13)(14). The general trend of IgM peaking at ≈1 month after symptom onset and IgG peaking at 2-4 months was consistent among different studies.…”
Section: Discussionsupporting
confidence: 88%
“…With a large number of patients who had confi rmed transmission history (176) and a complete dataset for 18, the level of confi dence is high that the results obtained in this study are representative for convalescent SARS patients. Similar results have been reported from longitudinal stud-ies of SARS patients with smaller cohort size (18-98 patients) and shorter follow-up period (240 days to 2 years) (9)(10)(11)(12)(13)(14). The general trend of IgM peaking at ≈1 month after symptom onset and IgG peaking at 2-4 months was consistent among different studies.…”
Section: Discussionsupporting
confidence: 88%
“…A more thorough investigation is needed to monitor the kinetic change of antibody levels over an extended period of time, including convalescence. Prior studies reported most individuals infected with SARS-CoV-1 mounted an antibody response [23][24][25] whereas MERS-CoV infected patients with mild or asymptomatic infections exhibited varied immune responses, which at times were undetectable by antibody assays [26,27]. While there is growing data on the antibody response to SARS-CoV-2 infection [18,28,29], the level and duration of the anti-SARS-CoV-2 antibodies in asymptomatic and mildly symptomatic COVID-19 patients is still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…To date, whether ADE occurs in SARS‐CoV infection in infected individuals is still controversial. Several clinical studies have reported that SARS‐CoV‐specific antibodies found in SARS patients are not harmful , whereas others have observed poor disease outcomes in early seroconverted SARS patients . To address this issue directly, it would be necessary to screen SARS patient sera, keeping in mind the possibility that ADE may only occur within a narrow window during the course of an infection and only in a subset of infected patients.…”
Section: Ade Is Exploited By a Variety Of Virusesmentioning
confidence: 99%